The prevalence of thyroid dysfunction in patients with connective tissue disorders - Jones, Dyna; Anjanappa, Jayashankar Chinnappa; Hiremath, Sourab; Siddaraju, Avinash; Hanumantha Reddy, Chandana Kandula; Sampoornam, Shalini Ashok; Manpreeth, Eashwer; Prashanthi, Seetha Venkata Sai Raghava (Asian Journal of Medical Sciences, 2021)
Background: Abnormalities in thyroid function have been reported in patients with connective tissue disorders. In India many patients suffer from thyroid dysfunction and rheumatological disorders. There is a lack of awareness of thyroid dysfunction in patients suffering from connective tissue disorders. Also, studies regarding the same are lacking in India. Aims and Objective: The current study was undertaken to estimate the Prevalence of Thyroid dysfunction in connective tissue disorders. Materials and Methods: It’s a duration based, prospective cross-sectional study including 100 patients. Patients presenting with connective tissue disorders were evaluated for thyroid function clinically and were subjected to serum TSH, Free T3, Free T4 and Anti-thyroid antibodies. The association was analyzed using frequency analysis, percentage analysis, and Chi-Square test. Results: Of the 100 patients in this study, predilection of connective tissue disorders was seen among females. The overall prevalence of thyroid dysfunction in patients with connective tissue disorder was 41%. 22% of the 100 patients had Anti-TPO antibodies suggestive of autoimmune thyroiditis. Our study showed 42.1% of the patients with rheumatoid arthritis, 45.5% of the patients with Systemic Lupus Erythematosus, 50% of the patients with Sjogren’s syndrome, 27.3% of the patients with Systemic sclerosis, and 42.9% of the patients with mixed connective tissue disorder had thyroid dysfunction. Conclusion: Our study demonstrates the increased prevalence of thyroid dysfunction among patients with connective tissue disorders and shows a female preponderance, in the age group of 45-65 years. Hence, early screening and intervention will prevent significant morbidity and improve the quality of patients’ life.